2013
DOI: 10.1021/ja406830d
|View full text |Cite
|
Sign up to set email alerts
|

Tryptophan-Accelerated Electron Flow Across a Protein–Protein Interface

Abstract: We report a new metallolabeled blue copper protein, Re126W122CuI Pseudomonas aeruginosa azurin, which has three redo sites at well-defined distances in the protein fold: ReI(CO)3(4,7-dimethyl-1,10-phenanthroline) covalently bound at H126, a Cu center, and an indole side chain W122 situated between the Re and Cu sites (Re-W122(indole) = 13.1 Å; dmp-W122(indole) = 10.0 Å, Re-Cu = 25.6 Å). Near-UV excitation of the Re chromophore leads to prompt CuI oxidation (<50 ns), followed by slow back ET to regenerate CuI a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
81
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(86 citation statements)
references
References 68 publications
(161 reference statements)
5
81
0
Order By: Relevance
“…In an earlier study we demonstrated that ETp across Trp with its conjugated indole side group is more efficient than through Ala with its saturated methyl side group (32). That result agrees with the known effects of Trp on ET in nature (33)(34)(35), such as acting as a redox-active "relay station" in hopping transport (19,33,36,37), and can be attributed to the indole, on the frontier orbitals of the peptide, i.e., a decreased highest occupied molecular orbitallowest unoccupied molecular orbital gap, because of lower ionization potential and increased electron affinity.…”
supporting
confidence: 82%
“…In an earlier study we demonstrated that ETp across Trp with its conjugated indole side group is more efficient than through Ala with its saturated methyl side group (32). That result agrees with the known effects of Trp on ET in nature (33)(34)(35), such as acting as a redox-active "relay station" in hopping transport (19,33,36,37), and can be attributed to the indole, on the frontier orbitals of the peptide, i.e., a decreased highest occupied molecular orbitallowest unoccupied molecular orbital gap, because of lower ionization potential and increased electron affinity.…”
supporting
confidence: 82%
“…65,66 Experiments that illustrated relatively fast electron self-exchange rates for the dimer focused on a high concentration of azurin, on the order of 1–2 mM. 67 Recently, a noncovalent dimer of rhenium-labeled azurin was reported to undergo tryptophan-mediated electron hopping through the protein interface; the dimer was found to exist at low concentrations near 70 μ M. 68 The present observation that reduction of Cu II Az proceeds quantitatively with formation of W48• strongly supports the presence of a dimer that enables interprotein ET under the present experimental concentrations of ∼50 μ M. An ET path through a dimer protein interface is proposed in the Supporting Information. In this dimer model, the ET path along the backbone and side chain is as follows: W48 in Zn II Az48W → T84 → H83→ across the protein– protein interface to N47 in Cu II Az48W → Cys112 → Cu II .…”
Section: Discussionmentioning
confidence: 99%
“…We have used Pseudomonas aeruginosa azurin as a test bed for mechanistic investigations of Trp and Tyr radical formation in protein ET reactions (Blanco-Rodriguez et al, 2011; Shih et al, 2008; Takematsu et al, 2013; Warren et al, 2012; Warren et al, 2013a). Our initial investigation revealed that Cu I oxidation by a photoexcited Re I -diimine complex (Re I (CO) 3 (4,7-dimethyl-1,10-phenanthroline)) covalently bound at His 124 on a His 124 Gly 123 Trp 122 Met 121 β-strand (ReHis 124 Trp 122 Cu I -azurin) occurs in a few nanoseconds, fully two orders of magnitude faster than documented for single-step electron tunneling at a 19-Å donor-acceptor distance, owing to a two-step hopping mechanism involving a Trp •+ radical intermediate (Shih et al, 2008).…”
Section: Radical Transfer Pathways In Azurinmentioning
confidence: 99%